GENİŞ CİLT KAYIPLARININ ONARIMINDA SERBEST LATERAL UYLUK FLEBİ - YÜCEL, Akın; AYDIN, Yağmur; SERADJMİR, Mesut and ÇETİNKALE, Oğuz (Cerrahpaşa Medical Journal, 2019)
Background and Design.- The flap alternatives for the reconstruction of wide skin defects are limited. Thigh region is a versatile area for numerous flaps with large skin islands. Lateral thigh flap was first described in 1983, but has not been popularized since then. We have used free lateral thigh flap for the reconstruction of six cases with wide skin defects caused by burn trauma. Results.- The mean age of the patients was 24 years (5 to 46 years). Three flaps were transferred to the neck and others to the extremities. The mean size of the flaps was 21x11 cm. Donor sites were closed primarily in three cases. All flaps were survived except for one, which was lost during initial surgery due to pedicle injury. Three flaps necessitated defatting procedures subsequently. Mean follow-up period was 28 months (5 to 44 months). Conclusion.- Lateral thigh flaps provides large amount of good quality skin for the reconstruction of wide skin defects. It is one of the largest skin flap in human body. Flap dissection is relatively easy and pedicle length and caliber is adequate. When closed primarily, donor site deformity is acceptable. The major drawbacks of the method are the thickness of the flap that usually necessitates thinning procedures and donor site deformity when skin grafting is necessary.